Naturalistic arm movements during obstacle avoidance in 3D and the identification of movement primitives - Grimme, Britta; Lipinski, John; Schöner, Gregor (Experimental brain research, 2012)
By studying human movement in the laboratory, a number of regularities and invariants such as planarity and the principle of isochrony have been discovered. The theoretical idea has gained traction that movement may be generated from a limited set of movement primitives that would encode these invariants. In this study, we ask if invariants and movement primitives capture naturalistic human movement. Participants moved objects to target locations while avoiding obstacles using unconstrained arm movements in three dimensions. Two experiments manipulated the spatial layout of targets, obstacles, and the locations in the transport movement where an obstacle was encountered. We found that all movement trajectories were planar, with the inclination of the movement plane reflecting the obstacle constraint. The timing of the movement was consistent with both global isochrony (same movement time for variable path lengths) and local isochrony (same movement time for two components of the obstacle avoidance movement). The identified movement primitives of transport (movement from start to target position) and lift (movement perpendicular to transport within the movement plane) varied independently with obstacle conditions. Their scaling accounted for the observed double peak structure of movement speed. Overall, the observed naturalistic movement was astoundingly regular. Its decomposition into primitives suggests simple mechanisms for movement generation.